Gastric cancer surgery: historical background and perspective in Western countries versus Japan - Zhang, Chun-Dong; Yamashita, Hiroharu; Seto, Yasuyuki (Annals of Translational Medicine, 2019)
Gastrectomy plus D2 lymphadenectomy plays a decisive role in the management of resectable gastric cancer in Japan. Before recent advances in chemotherapy, Japanese surgeons considered that extensive surgery involving extended lymphadenectomy with combined resection of neighboring organ(s) was required to eliminate any possible lymphatic cancer spread and improve patient survival. This approach differs radically from that in Western countries, which aim to improve survival outcomes by multidisciplinary approaches including perioperative chemotherapy and/or radiotherapy with limited lymph node dissection. However, a randomized controlled trial conducted in Japan found that more extensive lymphadenectomy including the para-aortic lymph nodes provided no survival benefit over D2 lymphadenectomy. Splenic hilum dissection with splenectomy also failed to show superiority over the procedure without splenectomy in patients with proximal gastric cancer, except in cases with tumor invasion of the greater curvature. Furthermore, bursectomy recently demonstrated similar outcomes to omentectomy alone. Although “D2 lymphadenectomy” as carried out in Japan contributes to low local recurrence rates and good survival outcomes, the results of randomized controlled trials have led to a decreased extent of surgical resection, with no apparent adverse effects on survival outcome. Notably, gastrectomy with D2 dissection has tended to become acceptable for advanced gastric cancer in Western countries, based on the latest results of the Dutch D1D2 trial. Differences in surgical practices between the West and Japan have thus lessened and procedures are becoming more standardized. Japanese D2 lymphadenectomy for advanced gastric cancer is evolving toward more minimally invasive approaches, while consistently striving to achieve the optimal surgical extent, thereby promoting consensus with Western counterparts.